The Role of Social Media on Students' Perceptions of Academic and Social Success - Yuni Syahfitri; Dewi Fitria; Muhammad Ridho Munthe; Yolanda Anggra Lexa (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2026)
This study explores the role of social media in shaping university students' perceptions of academic and social success. Social media platforms have become integral to students' daily lives, influencing how they define and pursue success. The research investigates both positive and negative impacts of social media usage on students' academic achievements and social interactions. Findings indicate that when social media is used as a tool for academic support and peer collaboration, it positively correlates with higher academic performance and enhanced social engagement. Conversely, excessive or entertainment-focused use may distract students, leading to lower academic outcomes and social comparison stress. The study highlights the dual nature of social media as both a facilitator and a potential barrier to student success. Recommendations emphasize the importance of mindful and purposeful use of social media to maximize its benefits in academic and social domains. This research contributes to a deeper understanding of how digital environments influence student perceptions and outcomes in higher education.